Penampilan Ayam Broiler yang Diberi Protein Sel Tunggal (PST) Sebagai Sumber Protein Pengganti Tepung Ikan dalam Pakan - N Ramli; D M Suci; C B Aditya (Faculty of Animal Science, Bogor Agricultural University, 2004)
Two thousands Cobb strain DOC were kept for 4 weeks to evaluate the effect of feeding diets containing Single Cell Protein (SCP) on feed consumption, weight gain and feed conversion ratio. SCP was used at level 0.0%, 2.5%, 5.0%, 7.5% and 10.0% of ration dry matter to replace fish meal in the diet. Data showed that feed consumption increased for broilers received SCP at level 2.5% and decreased at level 7.5 and 10%. Weight gain improved for broilers fed SCP up to level 5%. Feed conversion ratio increased only when 10% SCP was used. It is concluded that SCP up to level of 5% can be used to replace fish meal in the broiler's diet. Key words: single cell protein, fish meal, feed conversion ratio, broiler